Potassium Requirement of Mature Oil Palm on Coastal Soils - Ahmad Tajudin, Mohamad Hashim (1999)
Oil palm grown in the coastal marine clay soils are very productive with fresh fruit bunches (FFB) yield ranging between 28-40 tonnes per hectare. The high yield is attributable to high yielding planting materials, good agronomic practices and sound fertilizer application programme. Of the three factors, fertilizer application is considered to be the most influencing factor in maintaining high yield. In oil palm nutrition, the main nutrients which are important for vegetative growth and production are nitrogen, phosphorus, potassium and magnesium. However, the responses of oil palm to potassium fertilizer application on coastal marine clay soils are low and varied between and within the soil series. There is no clear answer to this phenomenon and thus this study was undertaken to provide explanation on the potassium requirements of oil palm planted on coastal marine clay soils. In this study a series of trials were conducted. In the experiment studying the responses of mature oil palm to NPK fertilizer application, the results showed that application of NPK fertilizers significantly increased their respective nutrient levels in the pinnae, but the magnesium levels were not affected. On fresh fruit bunch (FFB) production, phosphorus and nitrogen fertilizer application recorded positive significant responses. On the other hand, potassium fertilizer application showed no relationship at all with FFB production. In the experiment studying the responses of oil palm to potassium fertilizer application, the results of experiments indicated that potassium fertilizer application had significantly increased the potassium levels in the rachis and petiole and to a small degree in the pinnae, but this did not result in a corresponding increase in vegetative growth and crop production. Trunk analysis also showed high potassium content with increasing rate of potassium fertilizer application. The high potassium levels in the vegetative parts as a result of potassium fertilizer application were excess uptake because such high levels of potassium did not result in improved crop production. Such excess uptake was considered as luxury consumption.